Prevalence and factors associated with the use of traditional medicine in individuals with hypercholesterolemia, hyperglycaemia, and arterial hypertension in Ecuador: results from a population-based study in two health districts - Marta Puig-García; Carmen López-Herraiz; Cintia Caicedo-Montaño; María Fernanda Rivadeneira; Juan Vásconez-Donoso; Gregorio Montalvo-Villacis; Ikram Benazizi-Dahbi; Lucy Anne Parker; CEAD group (BMC, 2024)
Abstract Background While traditional medicine (TM) is employed by a significant portion of the global population for managing health issues, clinical guidelines and state recommendations often overlook this practice. The aim of this study was to describe the frequency of use of TM to control 3 metabolic risk factors (MRF): hypertension, hypercholesterolemia, and hyperglycaemia; and the sociodemographic, economic, and clinical characteristics associated with the use of TM. Methods Cross-sectional descriptive study that analyses data obtained from a representative population survey in 2 health districts, one urban in the south of Quito and another in a forested rural area with diverse ethnic groups in Esmeraldas, Ecuador. We include 602 individuals with at least one MRF. We calculated the proportion of people reporting the regular use of TM (herbal or traditional remedy) to control their MRF and we assessed potential associations with sociodemographic, economic, and clinical characteristics with a multivariable logistic regression model. Results In two very different sociocultural contexts in Ecuador we found that use of TM to control MRF was frequent (39.4% in Esmeraldas, 31.1% in Quito), frequently in combination with CM. There is a notable percentage of people, 33.9% in Esmeraldas and 39.0% in Quito, who did not take any treatment for their MRF, and the remainder used CM alone. In both settings, an individual's education lever was significantly associated with TM use. Whereas in Quito individuals with higher education more frequently treated their MRF with TM (aOR 2.04, 95% CI 1.03-3.90), in the rural, hard-to-reach context of Esmeraldas, it was more frequent among people with no formal schooling (aOR: 3.76; 95%CI 1.59-8.88), as well as those of younger age (aOR by year: 0.97; 95% CI 0.95-0.99) and afro ethnicity (aOR: 2.13; 95%CI 1.02-4.45). Conclusion Traditional medicine is used by a significant proportion of the population in Ecuador, highlighting the need for a more accessible and intercultural healthcare approach. The health system should ensure access to the necessary information and resources for the management of their metabolic risk factors.